Case Study in Auditing: A Case Study on Internal Control and Evidence Gathering With Emphasis on the Application of Judgment in Audit Decision Making. - Lins, William C.; Burns, Thomas J. (The Accounting Review, 1980)
Abstract The article reviews the book "Case Study in Auditing: A Case Study on Internal Control and Evidence Gathering With Emphasis on the Application of Judgment in Audit Decision Making," by Donald H. Taylor and G. William Glezen.